Economic downturn and volunteering: Do economic crises affect content generation on Wikipedia? - Michael Kummer; Olga Slivko; Michael Zhang (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
In this paper, we address the impact of surging unemployment on online public good provision. Specifically, we ask how drastically increased unemployment affects voluntary contributions of content to the online encyclopedia Wikipedia. We put together a monthly country-level data set, which combines country specific economic outcomes with data on contributions to the online encyclopedia. As a source of exogenous variation in the economic state we use the fact that European countries were affected by the financial crisis in the US in September 2008 with different intensity. For European countries, we find that the economic downturn is associated with more viewership, which channels higher participation of volunteers in Wikipedia expressed in editing activity and content growth. We provide evidence for increased information search online or online learning as a potential channel of the change in public goods provision, which is a potentially important side effect of economic downturn.
Older version: http://hdl.handle.net/10419/122186; Is replaced by the following version: http://hdl.handle.net/10419/173091
Keywords: D29; D80; H41; J60; L17; 330; online platform; Wikipedia; public goods; unemployment; user generated content